Autocatalytic Mechanism in the Anaerobic Reduction of Metmyoglobin by Sulfide Species - Palermo, Juan Cruz (2023)
The mechanism of the metal centered reduction of metmyoglobin (MbFeIII) by sulfide species (H2S/HS−) under an argon atmosphere has been studied by a combination of spectroscopic, kinetic, and computational methods. Asymmetric Sshaped time-traces for the formation of MbFeII at varying ratios of excess sulfide were observed at pH 5.3 < pH < 8.0 and 25 °C, suggesting an autocatalytic reaction mechanism. An increased rate at more alkaline pHs points to HS− as relevant reactive species for the reduction. The formation of the sulfanyl radical (HS• ) in the slow initial phase was assessed using the spin-trap phenyl N-tert-butyl nitrone. This radical initiates the formation of S−S reactive species as disulfanuidyl/ disulfanudi-idyl radical anions and disulfide (HSSH•−/HSS•2− and HSS−, respectively). The autocatalysis has been ascribed to HSS−, formed after HSSH•−/HSS•2− disproportionation, which behaves as a fast reductant toward the intermediate complex MbFeIII(HS−). We propose a reaction mechanism for the sulfide-mediated reduction of metmyoglobin where only ferric heme iron initiates the oxidation of sulfide species. Beside the chemical interest, this insight into the MbFeIII/ sulfide reaction under an argon atmosphere is relevant for the interpretation of biochemical aspects of ectopic myoglobins found on hypoxic tissues toward reactive sulfur species.